Patient-Centered Care in the OR: Is This Possible? - Gabrielson, Anna (Operating Room Nurses Association of Canada Journal, 1997)
Patient-centered care can be practiced in high technology areas such as the operating room if caregivers develop an attitude of seeing their care delivery through the patient’s eyes. Through caring interactions with our patients, we can find out what matters most to them. It seems that the more complex our technology and the more bureaucratic our hospitals have become, the less respect and positive regard is being communicated to patients. In addition, time is becoming increasingly scarce in our busy operating rooms. However, it is not how much time we spend with our patients. Instead, it is how we are with our patients in these stressful moments before surgery. Using concepts of relational care discussed in current nursing literature, nurses can evolve from a technically dominant caregiving paradigm towards a humanistic paradigm that focuses on the patient’ s expressed needs. This enables our clients to experience health and healing in their context.